Deindividuation Tendency: Conflict Management among College Students - Fitra Marsela; Evi Rahmiyati; Shalliha Nurul Putri; Martunis Martunis (AL-ISHLAH: Jurnal Pendidikan, 2024)
The phenomenon of demonstrations and conflicts between student groups that occur often ends in riots. In this situation, it is suspected that many individuals in their psychological state experience deindividuation. Deindividuation tendency is the loss of individual self-identity because it has merged into the group which results in a lack of self-awareness and self-control in individuals so that sometimes it can result in the individual behaving deviantly from social norms. This study aims to describe the description of deindividuation tendency in students at Syiah Kuala University and to describe how conflict management can be done in students. This study uses mixed method with explanatory sequential design. The population in this study were undergraduate students in the even semester of the 2022/2023 academic year from 5 faculties at Universitas Syiah Kuala. The sample was taken with simple random sampling technique with the Slovin formula as many as 390 students. Data collection on quantitative methods uses a deindividuation scale which is arranged based on 3 aspects, namely Group Immersion, Anonymity and Reduced Identifiabilty. Data collection in qualitative methods use interview guidelines were prepared based on the three dimensions of democratic conflict governance. The results showed that most of the deindividuation in Syiah Kuala University students were classified in the moderate category, namely 197 (51%) students. Deindividuation in this moderate category means that students tend to experience deindividuation in certain situations such as when facing conflicts between groups and carrying out demonstrations.